Analisis Kebutuhan Pengembangan Bahan Ajar Mata Kuliah Anatomi Tumbuhan Di Program Studi Pendidikan Biologi Universitas Mahaputra Muhammad Yamin - Darmanella Dian Eka Wati (Pendidikan Biologi FKIP UMMY, 2022)
The problem faced in learning the Plant Anatomy course is that the time allocation provided is still not sufficient to achieve the planned competency target. So we need a teaching material that can make time and learning objectives more effective. Before compiling teaching materials, lecturers need to analyze the needs for developing teaching materials. So that the teaching materials developed are in accordance with the needs of users. Based on this background, I conducted a research entitled